From 'parallel world' to 'trading zone': How diabetes-related information from social media is (not) discussed in clinical consultations. (March 2023) - Kjærulff, Emilie Mølholm; Langstrup, Henriette
Abstract: In today's digital world, people with type 1 and 2 diabetes turn to peers on social media to access and share information. Some studies have addressed how such information is discussed in clinical consultations, but conceptual nuances are needed to account for the different ways information is discussed. In this article, we draw on semi-structured interviews with 19 clinicians and 25 people with diabetes to examine how diabetes-related information from social media is discussed in Danish outpatient clinical consultations. The data were collected from September 2020 to January 2021. We conceptualise how these discussions fall on a continuum of (dis)engagement with social media information represented by three metaphorical concepts: parallel world, border zone, and trading zone. On one end, social media resembles a parallel world disconnected from clinical consultations: people with diabetes do not bring up social media information and clinicians do not invite them to discuss it. The middle of the continuum is represented by a border zone in which people with diabetes present social media information and clinicians' reactions can either push back, maintaining social media as a parallel world, or support the formation of a trading zone. On the other end, clinical consultations resemble a trading zone: clinicians are open to social media information, invite people with diabetes to discuss it and acknowledge the value of social media. Furthermore, these discussions are often characterised by negotiation in which different perspectives are exchanged. We discuss the benefits and challenges of moving from the parallel world to the trading zone, arguing that discussions about social media information may help clinicians learn what people with diabetes gain from online peer interactions and enable them to offer their expertise to support people with diabetes as they navigate a complex world of online information. Highlights: People with diabetes access and share information on social media. Social media information tends to remain unarticulated in clinical consultations. In a metaphorical sense, social media resembles a parallel world. Clinicians' reactions to information can maintain or integrate the parallel world. Engaging with social media information enables clinicians to offer their expertise.